Design of Aging Smart Home Products Based on Radial Basis Function Speech Emotion Recognition - Wu, Xu; Zhang, Qian (Frontiers in Psychology, 2022)
The rapid development of computer technology and artificial intelligence is affecting people's daily lives, language is the most common way of communication in people's daily life. In order to apply the emotion information contained in voice signals to artificial intelligence products after analysis, this paper proposes a design based on voice emotion recognition for aging intelligent home products with RBF. The author first aimed at smart home design, the problem of weak adaptability and learning ability of the aging population, a speech emotion recognition method based on a hybrid model of Hidden Markov/Radial Basis Function Neural Network (HMM/RBF) is proposed. This method combines the strong dynamic timing modeling capabilities of the HMM model, and the strong classification decision-making ability of the RBF model, by combining the two models, the speech emotion recognition rate is greatly improved. Furthermore, by introducing the concept of dynamic optimal learning rate, the convergence speed of the network is reduced to 40.25s, and the operation efficiency is optimized. Matlab's simulation tests show that the recognition speed of the HMM / RBF hybrid model is 9.82% -12.28% higher than that of the HMM model and the RBF model alone, confirming the accuracy and superiority of the algorithm and model.